DIVINITAS DAN HUMANITAS DALAM HUKUM PIDANA ISLAM - Sodiqin, Ali (UIN Sunan Kalijaga Yogyakarta, 2017)
Islamic law from its source is divine law because it is based on God’s revelation, but from its implementation, Islamic law is human made law, which is interpretation of revelation. So that in Islamic law contained the side of divinity and humanity, absolute character on one side and relative on the other side. The implication, which is called Islamic law is all the interpretation of the revelations made by the mujtahids. In Islamic criminal law, that reality also occurs. Although the source is revelation, the humanity aspect receives an important attention in Islamic criminal law. The purpose of establishing Islamic criminal law is to uphold human rights, such as the right to life, the right to marry, the right to property, the right of self-esteem, the right to think, and other basic rights. The guarantee of human rights protection is also seen in the form of penal sanctions, law enforcement models and law enforcement orientations. Legal sanctions are not the goal of law enforcement but the means or strategies so that they are adaptable. Law enforcement refers to restorative justice involving perpetrators, victims, communities, and the state. The legal orientation is not only to resolve legal conflicts, but to enforce social defense.Kata Kunci: hak asasi manusia, jinayah, restorative justice, perlindungan sosial